New data on the genus Syndicus Motschulsky (Coleoptera: Staphylinidae: Scydmaeninae) from Yunnan, southern China - Zhou, De-Yao; Yin, Zi-Wei (Zootaxa, 2017)
A new species of the ant-like stone beetle genus Syndicus Motschulsky, S. (Semisyndicus) long Zhou & Yin, sp. n., is described from Yunnan, southern China. New collecting data of Syndicus (s. str.) himalayanus Franz in China is provided. At present, eight Syndicus species are known to occur in China. An identification key and a distributional map for these species are presented.